Comparison of the vibriocidal antibody response in cholera due to Vibrio cholerae O139 Bengal with the response in cholera due to Vibrio cholerae O1. - Qadri, F (1995)
Vibrio cholerae serogroup O139, now considered to be the second organism capable of causing epidemic severe dehydrating cholera, contains a capsular polysaccharide which makes it difficult for it to be used in the conventional vibriocidal antibody assay optimized for V. cholerae O1. After modification of the procedure, which involved the use of specific bacterial strains, a lower bacterial inoculum, and increased amounts of complement, the vibriocidal antibody responses to V. cholerae O139 were measured in acute- and convalescent-phase sera from 33 V. cholerae O139-infected and 18 V. cholerae O1-infected patients and in single serum samples from 20 healthy control subjects. The responses in these individuals to V. cholerae O1 strains were also determined. Significant elevations in the homologous antibody response were found only in the convalescent-phase sera from both groups of patients with cholera. These findings may explain the basis for the lack of heterologous protection between the two serogroups of V. cholerae. Healthy controls had higher background levels of vibriocidal antibody to V. cholerae O1 than to V. cholerae O139.